A scalable method to fabricate high-performance biomimetic membranes for seawater desalination: incorporating pillar[5]arene water nanochannels into the polyamide selective layer - Lim, Yu Jie (2022)
In this work, we explored the practicability of a nanochannel-based biomimetic membrane (NBM) incorporating pillar[5]arene water channels for seawater reverse osmosis (SWRO) desalination. Two classes of peptide-attached biomimetic channels, (pR)-pillar[5]arenes (pRPH) and (pS)-pillar[5]arenes (pSPH) were integrated into the selective layer of SWRO membranes via interfacial polymerization on the top side of a polysulfone (PSf) support membrane. Here, pSPH is a non-identical stereoisomer of pRPH and was used as a negative control to pRPH to elucidate the flux enhancement effect contributed by pRPH. The optimized NBM presented a water permeability of 2.52 L m-2 h-1 bar-1 and 99.5% rejection under SWRO testing conditions of 50 bar applied pressure and 32,000 mg/L NaCl as feed solution. The 62% permeability increment with reference to the control membrane is hypothesized to originate from hybrid polyamide layers that were rougher with more voids (higher effective surface area and lower hydraulic resistance for water transport) as well as the conceivable water transport pathways provided by the pRPH channels. The simulation results from module-scale modelling suggest that the optimized NBM could lead to 7.2% savings in specific energy consumption of the membrane unit stage (or reduce the required membrane area by 25%) with respect to the commercial SWC4-LD membrane. The performance of the optimized NBM was further assessed in a one-week desalination test using an actual seawater feed gathered from an SWRO plant in Singapore. The robust NBM exhibited stable performance and ∼28% higher water flux (42 L m-2 h-1) than SWC4-LD with a comparable rejection of 99.3%, suggesting the feasibility of pillar[5]arene-based biomimetic membranes for seawater desalination.